فعالية استخدام القصص المصورة في تكوين الجمل المفيدة لدى الطلبة في الفصل الرابع عدن الثانوي في المدرسة الثانويّة الدّينيّة بولاية كوالالمبور الاتّحاديّة = Effectiveness of using storyboards in forming useful sentences for form 4 students SMA MAIWP - Mat Isa, Mohd Farhan; Abdul Wahab, Amir Hamzah; Abdullah, Nur Azam; Abdul Rahim, Abdul Hadi (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2019)
استهدفت هذه الدراسة إلى مدى فعالية استخدام القصص المصورة في تكوين الجمل المفيدة لدى الطلبة في الفصل الرابع عدن الثانوي في مدرسة مجلس الشؤون الإسلامية الثانوية الدينية بولاية كوالالمبور الاتحادية. يواجه الطلبة المشكلة المتعلقة بتكوين جمل مفيدة في الامتحان. الجمل غير مفيدة وفيها أخطاء كثيرة نحويا وصرفيا وأسلوبيا. فبناء على هذه الظاهرة، يودّ الباحثون معرفة مدى فعالية استخدام القصص المصورة في حل هذه المشكلة لدى الطلبة. فتكونت العينة من 25 طالبا من الفصل الرابع عدن الثانوي. قد قام الباحثون بإعطاء الطلاب قائمة من الأسئلة وتوزيع الاستبانة المتعلقة بهذه الدراسة. وبعد تحليل النتائج وجدوا أن استخدام القصص المصورة يساعد الطلاب في تكوين الجمل المفيدة. والاعتماد عليه أثناء عملية التعليم والتعلم يجعل البيئة ممتعة. ********************************************************************************************* This study aimed at the effectiveness of the use of comics in the formation of sentences for the students in the Form 4 Aden in Sekolah Menengah Agama Majlis Agama Islam Wilayah Persekutuan. The students are facing problem of creating useful sentences in the exam. The sentences have many grammatically, morphologically and stylistically errors. Based on this phenomenon, the researchers would like to investigate the effectiveness of using storyboards to solve this problem among the students. The population sample consisted of 25 students from the Form 4 Aden in the school. The researchers gave the students a list of questions and distributed the questionnaire related to this study. After analyzing the results, the researchers found that using storyboards help the students form comics in forming the sentences. Furthermore, relying on this methode during the teaching and learning process will make the learning environment enjoyable.